Mechanical and physical properties of Eucalyptus charcoal from pyrolysis under different conditions - Assis, Maíra Reis de (2016)
This research aimed to understand, experimentally, the mechanical behavior of a fixed bed of Eucalyptus charcoal blast furnace under different carbonization conditions. To attend the main goal, this study was divided into two phases: (i) destructive and non-destructive characterization of wood and charcoal produced at different carbonization temperatures. (ii) mechanical behavior of charcoal beds. Modulus of elasticity (flexion and compression), shear modulus, basic and apparent density, radial and tangential shrinkage and fiber saturation point were determined to evaluate wood properties. In a second step, wood samples were pyrolized at 500 °C and 900 °C. Apparent density, modulus of elasticity and shear modulus of charcoal samples were measured. Finally, the crushing strength was conventionally obtained by a static test in the three directions (longitudinal, radial and tangential). In a second phase, taking into account the procedures for the obtention of charcoal (500 and 900 °C), different granulometries (10 and 20 mm) and temperatures of compression bed tests (20 and 300 °C), a total of eight charcoal layers were made to evaluate the mechanical behavior of the granular medium. An apparatus consisting of a tube and a piston that is pushed by a universal test machine was prepared. The experiments consisted in carrying out repeated compression tests of controlled- sized charcoal with the apparatus. A particle size distribution is obtained as a function of the applied load, which is then classified by screening and weighing. Based on that, the particle size distribution is analyzed quantitatively. It was found that: (a) The charcoal MOE and apparent density increased with the final pyrolysis temperature, but the temperature effect was less significant for density. (b) Charcoal properties were higher for samples cut near the bark, but a high carbonization temperature seemed to reduce this phenomenon. (c) Charcoal is indeed, mechanical and physically, closely related with origin wood, independently of the final carbonization temperature. (d) The best predictor to estimate charcoal crushing strength was wood apparent density associated carbonization temperature and direction of compression. (e) The PCA indicated four groups, identified by different carbonization temperatures and particle sizes. However, the temperature effect of charcoal bed assays is not significant, since temperature is not a cumulative effect. (f) The dimension of fragments seems to be correlated with wood carbonization temperature. (g) Charcoal beds exposed to the highest compression temperature generally show less fragments in the > 8mm category.